INFECTIVITY AND HOST SPECIFICITY OF T. DANILEWSKYI STRAIN FCC-1 - M. S. Ahmed; K. Shafiq; H. Ali; W. A. Khan; F. Ollevier (Journal of Animal and Plant Sciences, 2012)
The parasite Trypanosoma danilewskyi strain FCc-1 was isolated from and maintained in juvenile common carps and was also cultivated in various culture media.  The present study was conducted to understand its ability of both blood stream forms (BSF) and culture forms (CF) to cause infection in common carp and also other fish species.  In the first experiment 3 groups of juvenile carps, each containing 20 fish were inoculated with 1000, 5000, 20,000 live T. danilewskyi strain FCc-1 per fish in all the treatment groups (groups A, B and C respectively), while the control group (D) only received 0.2 ml of PSG (phosphate buffered saline with glucose, pH 7, filter sterilized). The development of parasitemia (onset of infection) showed a similar pattern in all inoculated groups, although in group A, the peak of infection only appeared one week later compared with the two other groups (42 days instead of 35 days).  In a second experiment 9 groups, each containing 20 juvenile carps, were inoculated with 10,000 live trypanosomes (CF) per fish, but each group receiving a different strain; T. danilewskyi strain FCc-1, T. danilewskyi (Cac BR), T. danilewskyi (Caa 1), T. danilewskyi (Tt 1902), T. scardinii (Se BL), T. percae (Pf FR), T. boissoni and T. triglae (groups E to L) and ninth group M (control) received only 0.2 ml PSG). In group E the CF infection developed similar as the BSF one in the first experiment, while in groups F and G a significantly lower number of trypanosomes was detected in the fish blood, displaying very low infection peak. In all other groups (H-L) no trypanosomes were detected in the blood until day 98 p.i. In a third cross infection experiment, 8 groups belonging to different freshwater fish species (common carp, crucian carp, rudd, roach, perch, African catfish, brown bullhead and European eel) were inoculated with 10,000 live trypanosomes (BSF) per fish.  The T. danilewskyi strain FCc-1 involved was able to infect common carp and crucian carp, but not the other fish species.  In the fourth experiment trypanosomes were recovered from rudd and re-inoculated in 2 fish species; namely common carp and rudd. The infection developed in both hosts but in rudd the infection peak was very low.  From these experiments it appears that Trypanosoma danilewskyi strain FCc-1 is not strictly host specific and is able to infect other fish species belonging to the Cyprinidae.  Such infection is however not possible with fish hosts belonging to the Percidae, Anguillidae, Ictaluridae and Clariidae.
Keywords: Infectivity; Host specificity; Cross infections; Trypanosomes; Common carp